QuEChERS and UPLC-MS/MS-Based Quantification of Human Plasma of Eight Nucleoside Reverse Transcriptase Inhibitors and Platinum Anticancer Drugs for Hepatocellular Carcinoma - Yanan Liu; Jiangning Peng; Yan Liang; Yilin Li; Xiaolan Zhen; Hui Li (Molecules)
Nucleoside reverse transcriptase inhibitors (NRTIs) and platinum-based chemotherapeutics are widely utilized in cancer treatment. Evidence suggests that drug plasma concentrations are closely linked to both therapeutic efficacy and the risk of adverse effects. Consequently, developing therapeutic drug monitoring (TDM) methods is essential. Here, an effective procedure utilizing QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) techniques for preparing samples and UPLC-MS/MS for simultaneously measuring eight NRTIs and platinum-based drugs in human plasma is described. Chromatographic separation was conducted with an Agilent Eclipse Plus C18 column (4.6 × 100 mm, 3.5 μm) with acetonitrile with 0.1% formic acid as Phase A and 0.1% formic acid in water as Phase B, achieving complete separation within 10 min. The target analytes—lamivudine, telbivudine, emtricitabine, entecavir, tenofovir, nedaplatin, oxaliplatin, and adefovir dipivoxil—exhibited strong linearity within the 10–1000 ng/mL and 1–100 ng/mL ranges, showing correlations (r2) ≥ 0.9962. The method demonstrated excellent accuracy (−6.72% to 7.82%) and selectivity (84.53%–110.49%), as well as satisfactory recovery and stability. Overall, this analytical approach can be used to detect the combination of eight NRTIs and platinum-based drugs in human plasma. This method enables plasma drug-level monitoring in real time, with applications for individualized treatment approaches.